Pengaruh green strategy, CSR dan kinerja lingkungan terhadap kualitas laporan keuangan sektor makanan-minuman - Fitri Yuda; Febriati Febriati; Ali Afif (LPMP Imperium, 2026)
This study examined the influence of green strategy, CSR, and environmental performance on the quality of financial statements in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. This sector significantly contributes to Indonesia's GDP but faces environmental issues, such as waste and emissions, that affect reporting transparency. The analysis, based on a quantitative methodology using secondary data from the annual and sustainability reports of 22 companies over 3 years, was conducted in SPSS 27 using multiple regression. The findings revealed that while green strategy and CSR have a significant negative impact on financial statement quality due to high implementation costs, environmental performance positively influences quality by enhancing transparency and stakeholder trust. The study recommends expanding the sample size and the timeline for further research to enhance the generalizability of the results. Public interest statements This study aims to guide food and beverage manufacturing companies in enhancing financial report quality by implementing green strategies, strengthening CSR programs, and improving environmental performance. It highlights the importance of integrating sustainability into financial reporting to boost transparency, accountability, and stakeholder trust